Foreign Securities (Book). - Gray, Horace M. (The Accounting Review, 1930)
Reviews the book "Foreign Securities: Public and Mortgage Bank Bonds: An Analysis of the Financial, Legal, and Political factors," By John T. Madden and Marcus Nadler.